Reflection of M. E. Saltykov-Shchedrin’s Works in V. I. Semevsky’s Researches about Serfdom and Peasant Question in Russia - S. V. Gavrilov (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The study of the literary and journalistic image of serfdom and the peasant question in the works by M. E. Saltykov-Shchedrin, conducted by the prominent historian of the Russian peasantry V. I. Semevsky, is considered. The novelty of the work lies in the fact that it is devoted to the analysis of the first attempt to study the anti-serfdom content of the works of the outstanding Russian satirist and publicist as a historical source on the history of the Russian peasantry. The long-term process of V. I. Semevsky’s work on this topic is covered. It is shown that M. E. Saltykov-Shchedrin’s consideration of the peasant question is connected with the acute internal political struggle in the course of preparation and implementation of the peasant reform. The authors dwell on V. I. Semevsky’s assessments of the socio-cultural image of the Russian peasantry and nobility in the “Poshekhonskaya starina.” The proximity of the world outlook positions of the historian and the writer is revealed. Special attention is paid to the legal status of peasants in the process of preparation and implementation of the peasant reform. It is concluded that the brochure and articles by V. I. Semevsky about M. E. Saltykov-Shchedrin can be regarded as tools of ideological polemics with representatives of the conservative community, who sought to form nostalgia for pre-reform mores in Russian society and to rehabilitate them to some extent.